Development of student worksheets based on a metaphorical thinking approach with tutor feedback to improve students' mathematical connection ability - Maria Naimnule; Yohanes Jefrianus Kehi (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study aims to develop student worksheets based on a metaphorical thinking approach with tutor feedback to improve students’ mathematical connection ability in the topic of systems of linear equations in two variables. This research employed a development design based on the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The instruments used in this study included validation sheets, student and teacher response questionnaires, and mathematical connection ability tests. The validity assessment showed that the developed student worksheets obtained an average validity score of 93.06%, categorized as highly valid. The practicality test, based on student and teacher responses, obtained an average score of 84.5%, categorized as highly practical. The effectiveness of the worksheets was determined based on predefined criteria, namely the average achievement of students’ mathematical connection ability, classical mastery, and the difference between pretest and posttest scores. The results showed that the average posttest score reached 68.83, with classical mastery of 83.33%. In addition, students’ average score increased from 21.08 in the pretest to 68.83 in the posttest, and the paired sample t-test showed a significant difference with a sig. value of 0.000 < 0.05. These findings indicate that student worksheets based on a metaphorical thinking approach with tutor feedback are valid, practical, and effective for improving students’ mathematical connection ability.